SINTESIS DAN TRANSISI ELEKTRONIK SENYAWA KOMPLEKS KLOROFIL DENGAN LOGAM (M = Co2+, Fe3+) - Roberta Anjelia; Imelda Hotmarisi Silalahi; Gusrizal Gusrizal (Indonesian Journal of Pure and Applied Chemistry, 2019)
Metal complexes of chlorophyll (M = Co2+, Fe3+) have been prepared from a reaction of chlorophyll isolated from cassava leaves and metal precursors (CoCl2.6H2O or FeCl3) in methanol under reflux for 4 hours. FTIR spectra of the products indicated bond changes in chlorophyll structure particularly on absorption peaks with regard to N–H, N=C, C=C and C=O groups as a result of substitution of magnesium ion with cobalt(II) or iron(FE). UV-Vis spectra mainly showed hypsochromic shifts along with an increase in absorption intensity on Soret band area in the two complexes implying electronic effects of chlorin rings due to metal complexation.